THE NAMES OF FOREIGN MATHEMATICIANS IN MACEDONIAN - Celakoska-Jordanova, Vesna; Celakoska, Emilija (Matematichki Bilten, 2016)
In this paper we discuss the problem of pronunciation and transcription of the names of foreign mathematicians in the teaching of college mathematics and in mathematical literature in Macedonian. We adapt to the language rules and the transliteration challenges of the original names. Some examples from different textbooks and from the practice, which require pronunciation and transcription improvement, are given as well.